Implementasi Rekam Medis Elektronik pada Pelayanan Primer di Wilayah Kota Semarang: Analisis Determinan Individu dan Organisasi - Zefan Adiputra Golo; Asharul Fahyudi; Arief Azhari Ilyas; Titi Santika (Jurnal Penelitian Pendidikan IPA, 2023)
Implementing electronic medical records (EMR) in Puskesmas faces various challenges and barriers that hinder system users. This study aims to identify the effects of individual and organizational factors on the implementation of EMR in Puskesmas located in Semarang City. The study was designed as a cross-sectional study and was conducted between August and September 2023. Participants were selected from five health centres representing five regions of Semarang city, and included 46 health professionals, including physicians, nurses, midwives, medical record keepers and IT staff. The survey was taken from a standardized questionnaire based on the Technology Acceptance Theory and Institutional Theory. The results showed that 34% of the respondents were between 20 and 30 years old, where 76.1% were female and 52.2% had a bachelor's degree, and were dominated by nurses, where the majority had 1-5 years of experience. The constant (a) of 1.770 indicates the value of the independent variables in increasing EMR usage. The regression coefficient of the individual factor variable of 0.207 has a positive effect on EMR implementation. Organisational factors negatively affect the implementation of EMR use. The test results found that individual factors partially and significantly (0.005 <0.05) affect the implementation of EMR utilised.